COMPREHENSIVE REVIEW OF GERIATRIC PHARMACOTHERAPY IN ADDRESSING CHALLENGES AND CONSIDERATIONS FOR ELDERLY PATIENTS - Yahya Hadi Salem Balhareth, Shaqraa Mohammed Ali Zarban, Ali Abdullah Saeed Al Fehran, Zohor Ali M Alessa, Rahique Saad Saeed Alhumaidi, Muhammad Mohsen Dhafer Al-Bahri, Ali Mohsen Dafer Al Bahri, Jaber Saleh Mohmmad Lesloum (Chelonian Research Foundation, 2022)
This thorough review focuses on the complexity of geriatric pharmacotherapeutics and tries to enhance understanding of factors that hinder it, considering specific elderly patients. Along with aging, the population also faces the rising complexity of medication management challenges such as polypharmacy, physiological changes, and comorbidities. The abstract encloses only the objectives and scope, and the significance of the review is given stress, which highlights the utmost importance of having good medication management for senior people. This review is built on the foundation of what has been researched and sets out to fill the gaps in our knowledge, thereby resulting in the development of clinical practice and the implication of better health outcomes for elderly patients. DVDTCF is based on the spectrum of disease prevalence, drug safety issues, DE prescribing tactics, and comprehensive drug management from a patient’s perspective. By systematically thinking about the research findings and policy implications for practice, the reviewing process provides helpful information for various healthcare choices, such as healthcare providers, researchers, and policymakers looking to address such specific issues with geriatric pharmacotherapy. The ultimate objective is to achieve individualized, patient-oriented care that strives to optimize the gains of therapy and minimize the possible adverse side effects of any treatment options in elderly patients with better life quality and health outcomes. Keywords: Geriatric pharmacotherapy, elderly patients, challenges, considerations, literature review, methods, discussion, conclusion, recommendations.